Percutaneous plating of tibial fractures in two dogs - Schmökel, H. G.; Hurter, K.; Schawalder, P. (Veterinary and Comparative Orthopaedics and Traumatology, 2003)
A trend toward minimally invasive procedures in the treatment of fractures in human patients is apparent in recent publications. Percutaneous plating is one method of fracture fixation, conceived to minimise soft tissue damage and preserve soft tissue and bone vascularity. The use of fewer screws, in longer bridging plates, is also a relatively new technique in the stabilisation of comminuted diaphyseal fractures in human patients. A combination of these techniques was applied in two dogs with comminuted tibial fractures.The plates were passed subfascially and the screws inserted through skin incisions over the proximal and distal ends of the plate. Follow-up radiographs revealed fracture healing with callus formation after four or five weeks. Percutaneous plating seems to be a useful technique in small animals. Further studies on larger numbers of patients are needed to define the benefits and the limitations of this technique.
Keywords: Biological fracture fixation; percutaneous plating; dog